1990
DOI: 10.1073/pnas.87.5.1993
|View full text |Cite
|
Sign up to set email alerts
|

Activation and blocking of neuronal nicotinic acetylcholine receptor reconstituted in Xenopus oocytes.

Abstract: Neuronal nicotinic acetylcholine receptor of the a4/non-a (a4/na) type was reconstituted in Xenopus oocytes after nuclear injection of cDNA expression vectors. Functional neuronal receptor was only formed when the two subunits a4 and na were coiniected, neither a4 nor na alone being effective. Responses to bath application of acetylcholine (AcCho) have been measured in voltage clamp. AcCho doses as low as 10 nM induce currents of up to 50 nA. Dose-response studies indicate a Kd of about 0.77 x 10-6 M and a Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 39 publications
10
79
2
Order By: Relevance
“…Thus, hexamethonium blocked about 50% of the outward currents but inhibited about 90% of the inward currents (see above). This voltage-dependent effect of hexamethonium has been employed to support the idea that this drug blocks nicotinic channels by entering into the open pores (Ascher et al 1979;Bertrand et al 1990). …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, hexamethonium blocked about 50% of the outward currents but inhibited about 90% of the inward currents (see above). This voltage-dependent effect of hexamethonium has been employed to support the idea that this drug blocks nicotinic channels by entering into the open pores (Ascher et al 1979;Bertrand et al 1990). …”
Section: Resultsmentioning
confidence: 98%
“…Fourth, in cells with no initial response to ACh or in which IACh had been blocked with hexamethonium, IACh+ATP has exactly the same amplitude and kinetics as IATP. It is also likely that this inhibitory interaction not only requires activation of receptors but might actually require channels to be open, since hexamethonium, a substance that is believed to be a nicotinic channel blocker (Ascher et al 1979;Bertrand et al 1990), prevents ACh effects on IATP. At least four different observations indicate that IACh+ATP are carried through both nicotinic and P2X channels and not only through one population of these channels.…”
Section: Discussionmentioning
confidence: 99%
“…Inward rectification of ACh-elicited currents has been reported in mammalian peripheral ganglion cells (Derkach, Selyanko & Skok, 1983;Mathie, Cull-Candy & Colquhoun, 1987;Yawo, 1989;Fieber & Adams, 1991), chromaffin cells (Hirano, Kidokoro & Ohmori, 1987;Maconochie, 1990), and some central nervous system cells (Mulle & Changeux, 1990;Zhang & Feltz, 1990). In addition, macroscopic currents of neuronal nicotinic receptors composed of ac7 or a4 and na subunits reconstituted in Xenopus ooctyes have been reported to be inwardly rectifying (Bertrand, Ballivet & Rungger, 1990;Couturier, Bertrand, Matter, Hernandez, Bertrand, Millar, Valera, Barkas & Ballivet, 1990). In contrast to muscle-type receptors where the weak inward rectification can be explained by the voltage dependence of the apparent channel closing rate (Dionne & Stevens, 1975), the mechanisms underlying the inward rectification of ACh-elicited currents in ganglion cells have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ten different genes encoding neuronal nAChR subunits have been cloned and characterized in the chicken (a2 -(x8, nc I-naz3; Nef et al, 1988;Couturier et al, 1990a,b;Schoepfer et al, 1988Schoepfer et al, , 1990Hernandez,M.-C., in preparation) and in the rat (a2-a5, ,32-34; Boulter et al, 1986Boulter et al, , 1990Goldman et al, 1987;Wada et al, 1988;Deneris et al, 1988Deneris et al, , 1989Duvoisin et al, 1989;Isenberg and Meyer, 1989). Reconstitution studies in the Xenopus oocyte system have shown that the a2, a3 and a4 subunits can each lead to assembly of a functional nAChR in association with either na 1 or na3 and that each of these six receptors has specific physiological and pharmacological properties Wada et al, 1988;Bertrand et al, 1990;Couturier et al, 1990a). In contrast, the a7 and a8 subunits form homomeric receptors.…”
Section: Introductionmentioning
confidence: 99%